Viewing animal bodies: truths, practical aesthetics and ethical considerability in UK livestock breeding - Holloway, Lewis; Morris, Carol (Routledge, 2014)
This paper focuses on the production of aesthetic ‘truths’ in UK livestock breeding, drawing on detailed qualitative research with breeders and breed societies. It extends emerging interest in the aesthetic in human geographical research, examining how aesthetic judgements about non-human animals depend, in part, on the agency of the animal and their inter-subjective relations with humans in specific places. Aesthetic evaluation further produces implicit judgements about animals' ethical considerability, at the same time obscuring the effects of such judgements on their framing and treatment. Aesthetic evaluation is thus related to sets of material and ethical interests. The paper develops a more-than-human reading of Foucault's biopower, which explores how truths about visual evaluations of animals become established. Two empirical perspectives explore, first, a ‘relational practical aesthetic’ for evaluating beef cattle and sheep, exploring the implications of the aesthetic framing of specific animals and, second, the tensions involved in looking at animals when different aesthetic truths conflict and when traditions of aesthetic evaluation encounter genetic modes of evaluation. The paper concludes by discussing the ethical implications of ongoing transformations of evaluative modes in livestock breeding, suggesting that shifts away from inter-subjective modes of aesthetic evaluation further diminish the ethical status of animals.